Identification and validation of the important role of tryptophan-related gene CYP1B1 in the development and progression of sepsis - Li-Hong Chen; Wei-Ru Lin; Hui-Rong Hu; Zhi-Yuan Chen; Yan-Hui Wang (PLoS ONE, 2025)
Background Tryptophan metabolism is involved in the progression and immune response of multiple diseases. However, the function of tryptophan metabolism in the immune characteristics of sepsis still needs to be elucidated. Methods We collected the datasets from the GEO database to extract data of blood samples RNA of patients with or without sepsis in GSE28750, GSE65682, GSE69528, and GSE137342. A serials of bioinformatics analysis, including batch normalization, differential analysis, and single-cell sequencing analysis were finished through R software. Finally, the effects of the candidate differential gene on sepsis progression were evaluated using transcription-quantitative polymerase chain reaction (RT-qPCR), transwell assays, western blot, and immunofluorescence staining. Results One tryptophan metabolism-related DEG for sepsis were obtained, namely CYP1B1. The transcriptional and translational level of CYP1B1 were obviously increased in the blood tissues. Notably, CYP1B1 exhibited great discriminative ability for the diagnosis of sepsis. Furthermore, single-cell sequencing analysis further indicated that CYP1B1 was primarily expressed in monocytes, and its’ expression level was significantly upregulated in monocytes activated by sepsis/LPS. Knockdown of CYP1B1 dramatically decreased the proinflammatory cytokines expression, blocked the migration of monocytes, and inhibited the expression of tryptophan metabolism-related protein TDO2. Conclusion CYP1B1 is involved in tryptophan metabolism and its upregulation can promote the progression and development of sepsis through activating monocytes.